Ornamental Motifs in the Wall Paintings of the 17th–18th centuries in the Wooden Churches of Trsanscarpathia - Nesterenko, Andrii (HUDPROM: The Ukrainian Art and Design Journal, 2024)
This article presents the first analysis of ornamental motifs of the 17th–18th centuries in the sacral painting of Transcarpathia, based on preserved paintings in wooden churches in the villages of Kraynikovo, Novoselytsia, Kolodne, Oleksandrivka, Sokyrnytsia. The study highlights that ornamental art in Transcarpathia during this period developed in a distinctive manner due to the region’s geographical location and its diverse ethnic composition. European artistic trends reached Ukraine through the western territories, including Moldova, Slovakia, the Czech Republic. Until the 17th century, artistic influences primarily came from France and Italy, whereas in the 17th–18th centuries, Germany and the Netherlands played a significant role. Certain ornamental motifs, such as depictions of tulips, carnations, and a halved pomegranate, were introduced from Macedonia, Mount Athos, and Greece. Close artistic connections existed between Romanian Suceava and Ukrainian Lviv. Simultaneously, Ukrainian art centers in Kyiv and Galicia were actively flourishing during the 17th–18th centuries. The development of ornament in the wall paintings of wooden churches in Transcarpathia was also influenced by historical events in the region, which led to the cultural assimilation of Ukrainians with Romanians, Czechs, Slovaks, etc. This contributed to the enrichment of decorative patterns with motifs from various national traditions. It was revealed that the formation of ornamentation in Transcarpathia evolved in parallel with the formation and development of stylistic trends in Ukrainian art. In the 17th century, in the church art of this region, echoes of the Renaissance style blended with elements of Ukrainian folk art, and at the turn of the 17th–18th centuries, Ukrainian art as a whole developed under the influence of the Western European Baroque style, which stimulated an increased emphasis on ornamental decoration in church wall paintings. Handwritten books and a powerful folklore background served as a model for ornamental motifs for artists. The most widespread in Transcarpathia were plant-based patterns, the “zigzag” element, the image of a “pigtail”, and a grapevine motifs. The ornamental compositions in the wall paintings of the 17th–18th centuries in the churches of the villages of Kraynikovo, Novoselytsia, Kolodne, Oleksandrivka, Sokyrnytsia in Transcarpathia reflected the influences on the structure of the ornamental composition of the Ukrainian folk decorative and applied art and the artistic creativity of other nations. These ornaments not only decorated iconographic compositions, but also stood as independent works of art. The ornamental decoration of church wall paintings of the 17th–18th centuries of Transcarpathia vividly embodied the regional characteristics of the area’s artistic culture.